Investigation on waste materials as thermal insulation for building - Naji, Ihab Munther (2017)
Wall insulation is one of the most important things that can keep the surrounding temperature of the homes or any building suitable. It helps in maintaining the human comfort. The wall thermal insulation besides of keeping the area comfortable it may also help to achieve a reduction in consumption of energy while using heating or cooling systems of a house by saving energy and makes the surrounding area comfortable faster than usual. The aim of this research is to choose a potential material to be as a future thermal insulation. It focuses on waste materials such as coconut coir and cellulose. This research takes these two materials to test and analyses them using reconfigurable model house Marcraft GT-7500 and compare them with the results that have been gotten from common thermal insulations by making an experimental test for all these materials. Calculate the thermal effectiveness of each thermal material selected from the data that recorded. Various cases were conducted in reconfigurable model house to each of the materials that have been chosen. These cases are done by installing all material that selected sequentially in the cavities of a mini house and exposes different heat sources on them. Case one is using the ambient temperature as a heat source without any load. Case two is using an external heat source, while case three is done by using an internal heat source. All these three cases will help to give a much data to analyses and knowing the performance of materials when they are as a wall thermal insulation. At the end of the experiment, it shows that the coconut coir and the cellulose materials in a small gap comparing with the common thermal insulations and they can reliance on them in the future as thermal insulator for walls.